Identifikasi Jamur Penyebab Penyakit Utama pada Tanaman Selada (Lactuca sativa L.) Hidroponik - NI PUTU RATIH SUDIARTINI; GUSTI NGURAH ALIT SUSANTA WIRYA; I MADE SUDARMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2021)
Identification of the Fungal causal Agent of Main Diseases in Hydroponic Lettuce (Lactuca sativa L.) Hydroponics is an agricultural cultivation system without using soil but using water-containing nutrient solutions. Hydroponic technology is used as an alternative in plant cultivation to maintain optimal plant growth. It is completely protected from the influence of external elements such as rain, pests, climate, and others. One of the plants that are often cultivated in hydroponic technology is lettuce. However, in practice, hydroponic lettuce plants are also faced with the constraints of pathogenic fungi that cause disease in cultivated plants. This research was conducted to identify pathogenic fungi that cause disease in hydroponic lettuce plants. The results showed that the disease in hydroponic lettuce was a leaf spot disease caused by Cercospora sp. and wilt disease caused by Fusarium sp. Leaf spot disease is the main disease with a disease percentage of 41.90%.